Wrestlin' Jacob : A Portrait of Religion in Antebellum Georgia and the Carolina Low Country - Clarke, Erskine, 1941- (Book collections on Project MUSE., 2000)
"First published in 1979, Wrestlin' Jacob offers insights into the intersection of black and white religious history in the South. Erskine Clarke provides two arenas - one urban and one rural - that show what happened when white ministers tried to bring black slaves into the fold of Christianity. Clarke illustrates how the good intentions - and vain illusions - of the white preachers, coupled with the degradation and cultural strength of the slaves, played a significant role in the development of black churches in the South. The author's new introduction discusses the growth of interest in Southern religious history and reviews the scholarly developments in the field since the book's original publication."--Jacket